ANALISIS KESULITAN SISWA DALAM BELAJAR OPERASI PERKALIAN MATEMATIKA KELAS IV SD LEMAH RUBUH - Anjani Okatafianti, Atikah; Heru Purnomo (Widya Pustaka : Jurnal Ilmiah Pendidikan, 2025)
Elementary school is a crucial foundation for learning mathematics, especially multiplication operations. A strong conceptual understanding of multiplication is essential so that students do not merely memorize but truly comprehend the meaning behind the operation. However, many students, even in fourth grade, are still struggling to grasp the basic concept of multiplication. This study is a descriptive research with a qualitative approach aimed at identifying and describing students’ difficulties in understanding multiplication operations. Based on interviews with the fourth-grade homeroom teacher of SD Negeri Lemahrubuh, Mrs. Nur Halimah, it was found that many students have not yet mastered multiplication tables, do not understand the conceptual meaning of multiplication, and still rely on manual counting methods such as repeated addition, commonly referred to as the "fence method." Procedural errors are also frequently observed, particularly when solving multi-digit multiplication problems. Although the teacher has applied various teaching strategies—such as using visual aids, concrete media, and finger-counting techniques—the results have not been satisfactory. The findings of this study indicate that more interactive approaches, such as quick math games, motivational systems, and peer tutoring, are more effective in enhancing students’ understanding and learning motivation. This research is expected to contribute to the development of more innovative multiplication teaching methods that align with the characteristics and needs of elementary school students.